Synaptonemal complex damage in relation to meiotic chromosome aberrations after exposure of male mice to cyclophosphamide - Backer, L.C.; Gibson, J.B.; Moses, M.J.; Allen, J.W. (Mutation Research/Environmental Mutagenesis and Related Subjects, 1988)
The genetic implications of induced synaptonemal complex (SC) damage are not known. However, on theoretical grounds, such aberrations could be involved in mechanisms leading to potentially heritable defects. Cyclophosphamide (CP), a chemical reported to cause structural and numerical chromosomal aberrations in the mouse, was used to determine if SC damage observed in meiotic prophase is related to subsequent metaphase chromosomal aberrations. Male mice were injected i.p. with CP. In some instances, mice were also injected simultaneously with tritiated thymidine to label DNA so that cells could be tracked autoradiographically through spermatogenesis. Prophase, primary metaphase (M1), and secondary metaphase (M2) samples were sequentially harvested at appropriate times from the same individual, and nuclei were examined for aberrations. Correlation coefficients between SC and metaphase chromosome aberrations were calculated. The inclusion of tritium labeling increased the number and significance of positive correlations. Positive correlations were found between (1) dose-dependent total SC damage and damage to M1, and to a lesser extent, M2 chromosomes; (2) SC breaks/fragments and M1 chains/rings as well as isochromatid breaks/fragments; (3) SC asynapsis and M1 chromatid breaks/fragments; (4) SC multi-axial configurations and M1 chains/rings as well as isochromatid and chromatid breaks/fragments; and (5) SC multi-axial configurations and M2 hyperploidy. These correlations do not define mechanistic or causal relationships between SC and chromosomal damage. However, taken together with the observation that induced SC damage is many times greater than ensuing metaphase chromosome damage, they substantiate SC analysis as a highly sensitive indicator of potentially heritable effects of this (and presumably other) genotoxic agents.